Case Report: Two Cases of Recurring Ovale Malaria in Sarawak, Malaysia, after Successful Treatment of Imported Plasmodium falciparum Infection - Liew, Jonathan Wee Kent (Am J Trop Med Hyg, 2019)
Here are two cases of recurring ovale malaria in Sarawak, Malaysia, that are likely relapses that occurred 1–2 months after successful treatment of the initial imported falciparum malaria with artemisinin-based combined therapy. The patients have no history or recollection of previous malaria episodes. These cases add to the limited evidence on the relapsing nature of Plasmodium ovale, after a febrile episode. In regions where P. ovale is not known to be autochthonous, active follow-up of treated imported malaria patients is highly recommended following their return, particularly to areas nearing or having achieved elimination.